Long-term alkaline conditions inhibit the relative abundances of tetracycline resistance genes in saline 4-chlorophenol wastewater treatment. (April 2020) - Li, Yahe; Zhao, Jianguo; Li, Yu; Jin, Baodan; Zhang, Ke; Zhang, Hongzhong
Highlights: Except for 4-CP, the pollutants removal was inhibited in alkaline conditions. Alkaline conditions reduced TRGs production in saline 4-CP wastewater treatment. The stimulated proteins in EPS and microbial diversity affected the contents of TRGs. Selecting suitable carbon sources to achieve the removal of pollutants and ARGs. Abstract: Considering the occurrence and spread of antibiotic resistance genes (ARGs) pose significant risks to public health, the effects of long-term exposure to alkaline conditions on the relative abundances of tetracycline resistance genes (TRGs) were studied in saline 4-chlorophenol (4-CP) wastewater treatment. Alkaline conditions were maintained by supplying the co-metabolic carbon source of sodium acetate. Results showed that except for the 4-CP, the removal of pollutants was significantly inhibited, and the relative abundances of the most TRGs were repressed. In addition, the removal of pollutants and the relative abundances of TRGs were moderately affected by the NaCl addition. The proteins in the extracellular polymeric substances (EPS) played key roles in reducing the relative abundances of TRGs, which were altered by the microbial diversity. In conclusion, for the pollutants removal and ARGs reduction in refractory industrial wastewater treatment, alkaline conditions should be maintained by selecting suitable co-metabolic carbon sources.